Vitamin D Insufficiency in Adolescents: Results of Year-Round Screening in Moscow - I. N. Zakharova; T. M. Tvorogova; O. A. Gromova; E. A. Evseyeva; S. I. Lazareva; I. D. Maykova; N. G. Sugyan (Union of pediatricians of Russia, 2015)
Goal. Study of vitamin D sufficiency in children of puberty and pre-puberty age in Moscow. Methods. We examined children aged from 10 to 17 years living in Moscow. In order to appraise seasonal changes in the blood vitamin D status, we determined the average level of the main vitamin D metabolite - 25(OH)D - in different months of the year. The criteria for involving children into a laboratory examination were age (11-17 years), absence of organic or genetic pathology, permanent residence in Moscow, no intake of calcium and active vitamin D metabolite preparations at the time of examination. Results. The study involved 360 children (i. e. 30 children were examined every month) aged from 10 to 17 years. Analysis of the obtained data demonstrated differences in vitamin D sufficiency in the examined children in winter, spring, summer and autumn months. The serum concentration of vitamin D was significantly higher in summer months than in winter months. We did not reveal sex-related differences in vitamin D sufficiency among Moscow adolescents. Diet evaluation demonstrated that children extremely rarely consume fish as the main food source of vitamin D. Conclusions. Special attention should be given to the development of effective methods of correction of low vitamin D status and prevention thereof. Maintenance of the optimal vitamin D status in winter is infeasible due to insufficient exposure to sunlight, short duration of children's walking during the schoolyear and absence of cholecalciferol sources in children's diets. Special attention should be given to vitamin D intake by means of prescribing enriched food additives.